Review of cost versus scale: water and wastewater treatment and reuse processes - Guo, Tianjiao; Englehardt, James; Wu, Tingting (Water science and technology, 2014)
The US National Research Council recently recommended direct potable water reuse (DPR), or potable water reuse without environmental buffer, for consideration to address US water demand. However, conveyance of wastewater and water to and from centralized treatment plants consumes on average four times the energy of treatment in the USA, and centralized DPR would further require upgradient distribution of treated water. Therefore, information on the cost of unit treatment processes potentially useful for DPR versus system capacity was reviewed, converted to constant 2012 US dollars, and synthesized in this work. A logarithmic variant of the Williams Law cost function was found applicable over orders of magnitude of system capacity, for the subject processes: activated sludge, membrane bioreactor, coagulation/flocculation, reverse osmosis, ultrafiltration, peroxone and granular activated carbon. Results are demonstrated versus 10 DPR case studies. Because economies of scale found for capital equipment are counterbalanced by distribution/collection network costs, further study of the optimal scale of distributed DPR systems is suggested.